Lifeline infrastructure and the UN disaster resilience scorecard - M. Francis; M.R.Z. Whitworth (International Association of Lowland Technology, 2016)
The 2015 Nepal M 7.8 Earthquake and M 7.2 Aftershock caused catastrophic damage across a large area of strong shaking and impacting the entire nation. This paper presents best practices in evaluating core community functions in need, and planning for rapid and resilient recovery, building back better. Several tools and methods are explained including the concept of lifeline infrastructure resilience and performance goals under the 2015 United States (US) National Institute for Standards and Technology (NIST) Community Resilience Planning Guide; use of HazusMH loss modeling software adapted to measure losses avoided from modern hazard resistant building code provisions; and a framework for success using the new United Nations Disaster Resilience Scorecard, developed by IBM and AECOM, now piloted in over 30 cities since 2014 rollout. The utilization of the UNISDR scorecard for Kathmandu indicates the applicability of these techniques in evaluating the resilience of key infrastructure and institutional facilities, and how they can be an effective tool in planning and Disaster Risk Reduction.